Non‐toxigenic Vibrio cholerae in an autologous stem cell and renal transplant recipient. Issue 1 (6th July 2020) - Xu, Teena H.; Forrest, Graeme N
Abstract: A patient with a renal transplant after an autologous stem cell transplant for multiple myeloma developed non‐toxigenic Vibrio cholerae diarrhea after travel to Mexico. This is a rare cause of diarrhea in transplant recipients, and the patient had not had pre‐travel counseling. This case reflects the lack of referral of transplant recipients for travel infectious disease review before overseas travel and the role of the live attenuated cholera vaccine.